Mining and sustainable development in Peru - Sánchez Albavera, Fernando (2012)
It is a very opportune moment to analyze the effective contribution of mining to the sustainable development of our country, given the high degree of conflict in some mining operations and the emergence of anti-mining groups that oppose, without much argument, the development of a portfolio of investment projects that plan to start operations for some US$25 billion between 2012 and 2014. The economic success of President Ollanta Humala's administration will depend a lot on whether these projects can be carried out. I would like to provide some elements of judgment to open the debate, proposing an analytical framework to understand what has been the course of mining development in our country.